THE IMPACT OF CLIMATE CHANGE ON SOIL DEGRADATION AND ITS ECOLOGICAL CONSEQUENCES (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2026)
This article examines the impact of climate change on soil degradation and its ecological consequences. The study explores soil fertility decline, intensified erosion processes, and reduced biodiversity due to high temperatures, altered precipitation, and extreme climate events. Effective strategies to mitigate the socio-economic and ecological consequences of soil degradation are also proposed.